2016
DOI: 10.1016/j.otsr.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic outcomes in the coronal plane with iASSIST™ versus optical navigation for total knee arthroplasty: A preliminary case-control study

Abstract: III, prospective case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
1
22
1
1
Order By: Relevance
“…5 The combination of the accuracy of CAS with large console and the convenience of CON has been desired in recent years. Subsequently, portable accelerometer-based navigation devices (PADs) were introduced; these novel navigation systems mainly rely on accelerometer electronic components, 6 are superior to CASs in their low volumes and simpler procedures of navigation, and do not need inserting tracking pins, which helps avoid the associated risk of fractures. 7 Several studies have evaluated the efficiency of PAD by comparing it with CON.…”
mentioning
confidence: 99%
“…5 The combination of the accuracy of CAS with large console and the convenience of CON has been desired in recent years. Subsequently, portable accelerometer-based navigation devices (PADs) were introduced; these novel navigation systems mainly rely on accelerometer electronic components, 6 are superior to CASs in their low volumes and simpler procedures of navigation, and do not need inserting tracking pins, which helps avoid the associated risk of fractures. 7 Several studies have evaluated the efficiency of PAD by comparing it with CON.…”
mentioning
confidence: 99%
“…32 Several reports described high accuracy of TCA in MA-TKA using this navigation system. 16,33,34 Desseaux et al reported that the navigation system provided neutral mechanical axis rotation and optimal implant position in the coronal plane in 95% of cases using iASSIST. 33 Regarding tibial component accuracy, Kinney et al reported no outliers of more than 3 degree in postoperative tibial component alignment compared with the tibial mechanical axis using iASSIST.…”
Section: Discussionmentioning
confidence: 99%
“…16,33,34 Desseaux et al reported that the navigation system provided neutral mechanical axis rotation and optimal implant position in the coronal plane in 95% of cases using iASSIST. 33 Regarding tibial component accuracy, Kinney et al reported no outliers of more than 3 degree in postoperative tibial component alignment compared with the tibial mechanical axis using iASSIST. 16 Nam et al also reported that 97.6% of tibial components were implanted with an alignment of 90 AE 2 degree in the coronal plane using KneeAlign (OrthAlign Inc, Aliso Viejo, CA).…”
Section: Discussionmentioning
confidence: 99%
“…Our results coincide with previously published data that iAssist results are comparable to other navigation systems. 25 Bathis et al compared a Vector Vision CT free knee, Brain Lab, Munich, Germany) with Conventional technique and achieved mechanical axis of ±3° of valgus and/orvarus in 96% of navigational group compared to 78% in conventional group. 14 For a TKA performed in osteoarthritic knees with valgus and/or varus deformity, there are several specific procedures performed by the surgeon to achieve wellbalanced knee and a neutral mechanical axis by achieving slightly oblique bone resection in frontal and sagittal plane; releasing the soft tissues for a well-balanced stable knee and equal flexion and extension gaps.…”
Section: Discussionmentioning
confidence: 99%